The effectiveness of Kurikulum Merdeka on the accounting learning system in vocational schools - Alya Syafira Khairunnisa; Muhamad Ali; Najma Silma Nayyara; Talita Ardra Widyadhana (Himpunan Pengembang Kurikulum Indonesia, 2025)
Rapid developments in the world of education have encouraged curriculum changes in Indonesia, one of which is the Kurikulum Merdeka which emphasizes Merdeka Belajar. This study aims to explain the implementation, benefits, and challenges that arise in the learning process based on a Kurikulum Merdeka in the Accounting and Finance Expertise Program at SMK PGRI 1 Bandung. The Kurikulum Merdeka is designed to meet 21st-century learning needs by prioritizing Merdeka Belajar and practical skills development. The research method used is descriptive qualitative with a case study approach and literature, with a research focus on SMK PGRI 1 Cimahi. The results showed that the implementation of this new curriculum brought significant changes in the mastery of accounting materials and the improvement of students' practical skills. Although there are challenges in the adaptation process, such as reduced learning hours and teacher readiness, the flexibility of the curriculum allows teachers to adjust teaching methods according to student needs. This study recommends continuous evaluation of the implementation of the Kurikulum Merdeka to improve the quality of education in SMK and prepare students to face the challenges of the world of work. Abstrak Perkembangan pesat dalam dunia pendidikan telah mendorong adanya perubahan kurikulum di Indonesia, salah satunya adalah Kurikulum Merdeka yang mengedepankan “Belajar Mandiri”. Penelitian ini bertujuan untuk menjelaskan pelaksanaan, keuntungan, dan tantangan yang muncul dalam proses pembelajaran berdasarkan kurikulum merdeka pada Program Keahlian Akuntansi dan Keuangan Lembaga di SMK PGRI 1 Bandung. Kurikulum Merdeka dirancang untuk memenuhi kebutuhan pembelajaran abad ke-21 dengan mengedepankan kemandirian belajar dan pengembangan keterampilan praktis. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan pendekatan studi kasus dan literatur, memfokuskan pada SMK PGRI 1 Cimahi. Hasil penelitian menunjukkan bahwa penerapan kurikulum baru ini membawa perubahan signifikan dalam penguasaan materi akuntansi dan peningkatan keterampilan praktis peserta didik. Meskipun terdapat tantangan dalam proses adaptasi, seperti pengurangan jam belajar dan kesiapan pendidik, fleksibilitas kurikulum memungkinkan pendidik untuk menyesuaikan metode pengajaran sesuai kebutuhan peserta didik. Penelitian ini merekomendasikan evaluasi berkelanjutan terhadap implementasi Kurikulum Merdeka untuk meningkatkan kualitas pendidikan di SMK dan mempersiapkan peserta didik menghadapi tantangan dunia kerja. Kata Kunci: akuntansi; Kurikulum Merdeka; sistem pembelajaran akuntansi